(untitled) (Nigerian Journal of Cooperative Economics and Management, 2021)
The study focused on economic effect of covid-19 pandemic on thrift and credit cooperatives in Nigeria: Evidence from FCC (Oji River) Thrift and Credit Cooperative Society Limited. The objectives were to explore the economic effect of covid-19 on cooperative sector, to evaluate how the cooperative stakeholders’ addressed threat of the pandemic, and to assess the responses by the cooperative actors. Primary and secondary data were used for the study. The study was anchored on the theory of Epidemiologic Transition and Resource Dependence. Qualitative approaches were employed in describing the emerged economic effect of covid-19 pandemic on thrift and credit cooperative societies. Results showed that cooperative principles were compromised during the pandemic, where monthly meetings and AGMs were suspended. There was limited loan recovery, decrease in members’ savings and deposit, liquidity risk, impracticability of democratic member control, difficulty in loan acquisition from financial institutions, among other findings. The paper observed that the pandemic presented an opportunity for the innovation in techniques and digitalization in operations of the cooperative sector, and recommended that ICOPRON, CFN, and Apex organizations should strive to improve connectivity to revive the cooperative sector in post pandemic era.